KOMPETENSI GURU DALAM MENYUSUN PERENCANAAN PEMBELAJARAN YANG BERKUALITAS - Fatma Azzahra; agus Rohimat; Carsiwan (LPPM Universitas Cipta Mandiri, 2026)
Education is an important factor in improving the quality of human resources, and teachers play a strategic role in determining the success of the learning process. One of the essential competencies that teachers must possess is the ability to develop high-quality lesson planning as a guide for conducting effective and well-directed learning activities. This study aims to analyze teachers' competencies in developing quality lesson plans and identify the factors influencing those competencies. The study employed a qualitative approach using a literature review method. Data were collected from national and international scientific journals, books, and educational policy documents published between 2020 and 2025. The analysis process utilized the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, which includes identification, screening, eligibility assessment, and inclusion stages. The findings indicate that teachers' competencies in lesson planning are influenced by pedagogical competence, curriculum mastery, teaching experience, professional training, and the ability to understand students' characteristics. Teachers with strong lesson-planning competencies are more capable of designing effective, innovative, adaptive, and student-centered learning processes. Conversely, inadequate lesson-planning competence may negatively affect the effectiveness of learning implementation. This study also emphasizes that the quality of lesson planning is not merely determined by the completeness of instructional documents but also by teachers' ability to design contextual learning experiences that align with students' needs and the demands of the Merdeka Curriculum.